Highly efficient production of rebaudioside D enabled by structure-guided engineering of bacterial glycosyltransferase YojK - Guo, Baodang; Hou, Xiaodong; Zhang, Yan; Deng, Zhiwei; Ping, Qian; Fu, Kai; Yuan, Zhenbo; Rao, Yijian (Frontiers in Bioengineering and Biotechnology, 2022)
Owing to zero-calorie, high-intensity sweetness and good taste profile, the plant-derived sweetener rebaudioside D (Reb D) has attracted great interest to replace sugars. However, low content of Reb D in stevia rebaudiana Bertoni as well as low soluble expression and enzymatic activity of plant-derived glycosyltransferase in Reb D preparation restrict its commercial usage. To address these problems, a novel glycosyltransferase YojK from Bacillus subtilis 168 with the ability to glycosylate Reb A to produce Reb D was identified. Then, structure-guided engineering was performed after solving its crystal structure. A variant YojK-I241T/G327N with 7.35-fold increase of the catalytic activity was obtained, which allowed to produce Reb D on a scale preparation with a great yield of 91.29%. Moreover, based on the results from molecular docking and molecular dynamics simulations, the improvement of enzymatic activity of YojK-I241T/G327N was ascribed to the formation of new hydrogen bonds between the enzyme and substrate or uridine diphosphate glucose. Therefore, this study provides an engineered bacterial glycosyltransferase YojK-I241T/G327N with high solubility and catalytic efficiency for potential industrial scale-production of Reb D.